Evaluation of Atmospheric Boundary Layer Height From Wind Profiling Radar and Slab Models and Its Responses to Seasonality of Land Cover, Subsidence, and Advection. Issue 7 (29th March 2021) - Rey‐Sanchez, Camilo; Wharton, Sonia; Vilà‐Guerau de Arellano, Jordi; Paw U, Kyaw Tha; Hemes, Kyle S.; Fuentes, Jose D.; Osuna, Jessica; Szutu, Daphne; Ribeiro, João Vinicius; Verfaillie, Joseph; Baldocchi, Dennis
Abstract: In this study, we evaluated the effect of land cover, atmospheric subsidence, and advection on the annual dynamics of atmospheric boundary layer (ABL) height from two contrasting sites. The first site is the Walker Branch forest, a deciduous forest of temperate climate, complex topography, and cloudy summers. The second site is the Sacramento‐San Joaquin River Delta, a site of Mediterranean climate, flat terrain on a local scale, and clear summers. After testing a new algorithm to calculate ABL heights from 915 MHz radar wind profilers, we evaluated a hierarchy of three slab models to recreate the diurnal and annual patterns of ABL growth. We found that the lower ABL heights in the Delta, particularly during late summer, are driven by the combined effects of increased atmospheric subsidence and marine air advection. In both sites, the annual pattern of ABL height was strongly correlated to total daily incoming radiation, and in the Delta, the annual pattern of ABL height closely followed the seasonal patterns of sensible heat flux from a mosaic of different land covers. A land composite of latent and sensible heat fluxes obtained through a meso‐network of eddy covariance measurements and the ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) mission resulted in higher model skill, thus showing that land cover heterogeneity is an important driver of ABL growth. Model simulations show that in the Delta, restoring agricultural land to wetlands with large open water areas could result in a reduction of ABL height during those months with low subsidence and advection. Plain Language Summary: The height of the atmospheric boundary layer drives the dilution of contaminants and other trace gases; therefore, it is of vital importance for the creation of accurate atmospheric and weather models. In this study, we report on comparisons of boundary layer height from radar wind profilers against three models with different levels of complexity in two sites with contrasting land covers. The first site is the Walker Branch forest, a forest of temperate climate, complex topography, and cloudy summers. The second site is the Sacramento‐San Joaquin River Delta in California, a site of Mediterranean climate, flat terrain, and clear summers with high rates of atmospheric subsidence and cold‐air advection from the adjacent ocean. We demonstrate that the annual cycle in boundary layer height is mostly driven by daily solar radiation in both sites; however, the presence of different land covers also has an important effect on driving the boundary layer height annual pattern, especially for those times where there is low atmospheric subsidence and advection. These results can help to understand the effects of changes in land cover on the boundary layer height and the air quality within it. Key Points: Atmospheric boundary layer (ABL) height is studied using radar wind profilers and slab models in two contrasting ecosystems over annual time scales Atmospheric subsidence and cold‐air advection limit the growth of the boundary layer during the summer in Northern California Land‐cover‐mediated changes in ABL height are important but muted by strong subsidence and advection